One-pot synthesis of α-aminophosphonates via a cascade sequence of allylamine isomerization/hydrophosphonylation. Issue 32 (5th April 2017) - Mao, Liu-Liang; Li, Chen-Chen; Yang, Qiang; Cheng, Ming-Xing; Yang, Shang-Dong
Abstract : A Rh/Ni-catalyzed cascade sequence of allylamine isomerization and hydrophosphonylation to synthesize α-aminophosphonates has been disclosed. Abstract : A Rh/Ni-catalyzed cascade sequence of allylamine isomerization and hydrophosphonylation to synthesize α-aminophosphonates has been disclosed. The reaction, which not only allows the generation of widespread valuable α-aminophosphonates under simple systems and mild conditions, but also enriches the process of olefin isomerization–addition both in catalytic systems and various reaction types.